Deficits in the vesicular acetylcholine transporter alter lifespan and behavior in adult Drosophila melanogaster. (July 2020) - White, Daniel; de Sousa Abreu, Raquel P.; Blake, Andrew; Murphy, Jeremy; Showell, Shardae; Kitamoto, Toshihiro; Lawal, Hakeem O.
Abstract: The neurotransmitter acetylcholine (ACh) is involved in critical organismal functions that include locomotion and cognition. Importantly, alterations in the cholinergic system are a key underlying factor in cognitive defects associated with aging. One essential component of cholinergic synaptic transmission is the vesicular ACh transporter (VAChT), which regulates the packaging of ACh into synaptic vesicles for extracellular release. Mutations that cause a reduction in either protein level or activity lead to diminished locomotion ability whereas complete loss of function of VAChT is lethal. While much is known about the function of VAChT, the direct role of altered ACh release and its association with either an impairment or an enhancement of cognitive function are still not fully understood. We hypothesize that point mutations in Vacht cause age-related deficits in cholinergic-mediated behaviors such as locomotion, and learning and memory. Using Drosophila melanogaster as a model system, we have studied several mutations within Vacht and observed their effect on survivability and locomotive behavior. Here we report for the first time a weak hypomorphic Vacht allele that shows a differential effect on ACh-linked behaviors. We also demonstrate that partially rescued Vacht point mutations cause an allele-dependent deficit in lifespan and defects in locomotion ability. Moreover, using a thorough data analytics strategy to identify exploratory behavioral patterns, we introduce new paradigms for measuring locomotion-related activities that could not be revealed or detected by a simple measure of the average speed alone. Together, our data indicate a role for VAChT in the maintenance of longevity and locomotion abilities in Drosophila and we provide additional measurements of locomotion that can be useful in determining subtle changes in Vacht function on locomotion-related behaviors. Highlights: Deficits in Vacht function cause an allele dependent effect in organismal survival. Demonstration of involvement of acetylcholine in thigmotaxis-like behavior. Differential role for acetylcholine signaling in regulating specific behaviors. First report of a weak hypomorphic Vacht point mutant allele in Drosophila .